Solid waste debris management on selected beaches in Malaysia / Khairunnisa Ahmad Kamil - Ahmad Kamil, Khairunnisa (2012)
Solid waste debris on beaches had caused environmental, aesthetical, economic and social problems in Malaysian beaches. This study discussed solid waste debris management on selected Malaysian beaches namely, Teluk Kemang, Pasir Panjang, Batu Burok, Seberang Takir, Tanjung Aru and Teluk Likas. The objectives of the study are to determine the abundance, composition, rate of accumulation, and the sources of debris on these beaches. It also aims to investigate the current beach management in Malaysia and beach users’ opinion and attitude towards marine pollution issues. Debris from a total area of 60 m along each beach were collected, separated, counted, and weighed. As for the users’ opinion, a total number of 180 beach users were interviewed. Results indicated that the highest abundance of debris was found in Seberang Takir beach at a density of 15.5 g/ m2 with approximately 138 items every 10 m2 areas. Plastic was the most abundant type of debris found regardless of the function of the beach. Recreational, fishing and shipping activities are among the sources of debris on studied beaches. Natural event such as monsoon, and beach management also played a significant factor to the presence of debris on beaches. Beach users were found to have low awareness regarding marine pollution issues. Therefore, future beach management should look into all aspects of concern in order to mitigate the debris problem on Malaysian beaches.